Transcriptome analysis reveals a lncRNA-miRNA-mRNA regulatory network in OsRpp30-mediated disease resistance in rice - Minghua Li; Wei Li; Meixia Zhao; Zhiqiang Li; Guo-Liang Wang; Wende Liu; Chun Liang (BMC Genomics, 2023)
Abstract Background Long non-coding RNAs (lncRNAs) play critical roles in various biological processes in plants. Extensive studies utilizing high-throughput RNA sequencing have revealed that many lncRNAs are involved in plant disease resistance. Oryza sativa RNase P protein 30 (OsRpp30) has been identified as a positive regulator of rice immunity against fungal and bacterial pathogens. Nevertheless, the specific functions of lncRNAs in relation to OsRpp30-mediated disease resistance in rice remain elusive. Results We conducted a comprehensive analysis of lncRNAs, miRNAs, and mRNAs expression patterns in wild type (WT), OsRpp30 overexpression (OsRpp30-OE), and OsRpp30 knockout (OsRpp30-KO) rice plants. In total, we identified 91 differentially expressed lncRNAs (DElncRNAs), 1671 differentially expressed mRNAs (DEmRNAs), and 41 differentially expressed miRNAs (DEmiRNAs) across the different rice lines. To gain further insights, we investigated the interaction between DElncRNAs and DEmRNAs, leading to the discovery of 10 trans- and 27 cis-targeting pairs specific to the OsRpp30-OE and OsRpp30-KO samples. In addition, we constructed a competing endogenous RNA (ceRNA) network comprising differentially expressed lncRNAs, miRNAs, and mRNAs to elucidate their intricate interplay in rice disease resistance. The ceRNA network analysis uncovered a set of gene targets regulated by lncRNAs and miRNAs, which were found to be involved in pathogen recognition, hormone pathways, transcription factor activation, and other biological processes related to plant immunity. Conclusions Our study provides a comprehensive expression profiling of lncRNAs, miRNAs, and mRNAs in a collection of defense mutants in rice. To decipher the putative functional significance of lncRNAs, we constructed trans- and cis-targeting networks involving differentially expressed lncRNAs and mRNAs, as well as a ceRNA network incorporating differentially expressed lncRNAs, miRNAs, and mRNAs. Together, the findings from this study provide compelling evidence supporting the pivotal roles of lncRNAs in OsRpp30-mediated disease resistance in rice.